2017
DOI: 10.1016/j.ijpsycho.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Shifting of attentional set is inadequate in severe burnout: Evidence from an event-related potential study

Abstract: Individuals with prolonged occupational stress often report difficulties in concentration. Work tasks often require the ability to switch back and forth between different contexts. Here, we studied the association between job burnout and task switching by recording event-related potentials (ERPs) time-locked to stimulus onset during a task with simultaneous cue-target presentation and unpredictable switches in the task. Participants were currently working people with severe, mild, or no burnout symptoms. In al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 97 publications
1
22
0
Order By: Relevance
“…However, as pointed out by the review's authors, not controlling for confounding variables, for example depression, may have led to an overestimation of the effects. Conversely, some other studies have found either no significant association of burnout with cognitive functioning (Castaneda et al, 2011;McInerney, Rowan, & Lawlor, 2012) or the signs of cognitive impairment were found only for groups displaying severe burnout symptoms (Oosterholt, Maes, Van Der Linden, Verbraak, & Kompier, 2014;Sokka et al, 2017). These inconsistencies in the literature regarding the link between burnout and objective cognitive functioning warrants further research.…”
Section: Introductionmentioning
confidence: 87%
“…However, as pointed out by the review's authors, not controlling for confounding variables, for example depression, may have led to an overestimation of the effects. Conversely, some other studies have found either no significant association of burnout with cognitive functioning (Castaneda et al, 2011;McInerney, Rowan, & Lawlor, 2012) or the signs of cognitive impairment were found only for groups displaying severe burnout symptoms (Oosterholt, Maes, Van Der Linden, Verbraak, & Kompier, 2014;Sokka et al, 2017). These inconsistencies in the literature regarding the link between burnout and objective cognitive functioning warrants further research.…”
Section: Introductionmentioning
confidence: 87%
“…Results from recent physiological and brain-imaging studies into non-clinical burnout are in line with these findings of the involvement of prefrontal cognitive functions. EEG studies indicate impairment in executive functioning in non-clinical burnout (reduced amplitude of the P300), for example, in attention shifting [22,23] and in response inhibition [24]. Clinically, people with such an impairment may be more easily distracted.…”
Section: Cognitive Functioning In Non-clinical Burnoutmentioning
confidence: 99%
“…Despite the fact that burnout has well-documented effects on psychophysical states, a limited number of studies have examined its influence on specific cognitive functions (e.g., van der Linden et al, 2005; Schmidt et al, 2007; Castaneda et al, 2011; Oosterholt et al, 2012, 2014; Deligkaris et al, 2014; Sokka et al, 2014, 2017; Giorgi et al, 2016). Regarding the broader context of the current economic situation (Mucci et al, 2016), the dynamics of workplace changes (Rachiotis et al, 2014; Giorgi et al, 2015), and the prevalence of work-related stress and burnout problems, it is particularly important to study its impact on mental health, well-being and individual functioning.…”
Section: Introductionmentioning
confidence: 99%